2018
DOI: 10.4274/jtgga.2017.0045
|View full text |Cite
|
Sign up to set email alerts
|

Dual trigger with gonadotropin-releasing hormone and human chorionic gonadotropin for poor responders

Abstract: Objective:To compare metaphase II (MII) rate, fertilization rate, and embryo quality with dual trigger gonadotropin-releasing hormone agonist (GnRH) and normal dose human chorionic gonadotropin (hCG) versus a normal dose hCG trigger in antagonist intracytoplasmic sperm injection (ICSI) cycles of poor ovarian responders.Material and Methods:Patients defined as poor ovarian responders according to the Bologna criteria who underwent ICSI with GnRH antagonist protocol and triggered with dual trigger or hCG alone f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…However, other studies have found dual-trigger to be ineffective at improving IVF outcomes for this population. Eser et al [24], in a case control study involving 47 dual-trigger and 62 hCG only trigger cases fulfilling the Bologna criteria for POR, discovered no statistical different between the two groups with reference to implantation rate, biochemical pregnancy rate, clinical pregnancy rate, and ongoing pregnancy rate. Due to the divergence of opinion on the effectiveness and clinical utility of dual-trigger for final oocyte maturation, large scale randomized controlled trials are required to reach a verdict.…”
Section: Discussionmentioning
confidence: 97%
“…However, other studies have found dual-trigger to be ineffective at improving IVF outcomes for this population. Eser et al [24], in a case control study involving 47 dual-trigger and 62 hCG only trigger cases fulfilling the Bologna criteria for POR, discovered no statistical different between the two groups with reference to implantation rate, biochemical pregnancy rate, clinical pregnancy rate, and ongoing pregnancy rate. Due to the divergence of opinion on the effectiveness and clinical utility of dual-trigger for final oocyte maturation, large scale randomized controlled trials are required to reach a verdict.…”
Section: Discussionmentioning
confidence: 97%
“…With the extensive application of the GnRH antagonist scheme, GnRH-a has been used as an alternative trigger drug, which can effectively promote the release of endogenous FSH and LH to induce follicle maturation and ovulation, as well as embryo development and pregnancy rates which are similar to those obtained using hCG trigger [7]. Compared with hCG trigger, the duration of the LH surge is shortened, thereby the risk of OHSS was reduced [8]. The incidence of EFS after a GnRH-a trigger has similar rate with hCG trigger [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…With the extensive application of the antagonist scheme, GnRH-a is often used as a trigger drug, which can promote the release of endogenous FSH and LH to promote follicle maturation and induce ovulation in a short time. Compared with HCG, the duration of the LH surge is shortened, thereby reducing the risk of OHSS [9]. The incidence of EFS after a GnRH-a triggering has been reported to be 3.3% (9/271) [10].…”
Section: Discussionmentioning
confidence: 99%